Design and Application of a Design Platform for Multiple Megawatt Wind Turbines Controller - DU Jiajia; WAN Yubin; LIU Hongwen; WANG Dian; LU Yong (Kongzhi Yu Xinxi Jishu)
A platform of controller design for multiple megawatts wind turbines is designed. The platform can provide much more powerful functions and flexible configuration of power production and state supervision for controller prototype design. Based on the model of wind turbines and the simulated software GH Bladed, the designed platform can also be used for the full-digital simulation to assess the performance of controller prototype of different wind turbines, which would provide strong support for the controller design. Finally, the evaluation of the controller design platform with a 2.5 MW wind turbine is conducted and the evaluation results show that the accuracy in the controller model is very good, and the controller platform has wide application prospect.